OVERSEAS CHINESE BANKING CORPORATION CHILDREN DEVELOPMENT CO-SAVINGS (BABY BONUS) ACCOUNT - Tay, Charles (2010)
With effect from 1st August 2008, Overseas Chinese Banking Corporation (“OCBC”) and Standard Chartered Bank Singapore (“Stanchart”) had taken over from Development Bank of Singapore (“DBS”) as the managing agents for the Children Development Co-Savings (Baby Bonus) Accounts. After the concluded transfer exercise in November 2008, OCBC had since been the market leader with 76% of the market share.